Water’s Contribution to the Energetic Roughness from Peptide Dynamics - Johnson, Quentin; Doshi, Urmi; Shen, Tongye; Hamelberg, Donald (Journal of chemical theory and computation, 2010)
Water plays a very important role in the dynamics and function of proteins. Apart from protein−protein and protein−water interactions, protein motions are accompanied by the formation and breakage of hydrogen-bonding network of the surrounding water molecules. This ordering and reordering of water also adds to the underlying roughness of the energy landscape of proteins and thereby alters their dynamics. Here, we extract the contribution of water to the ruggedness (in terms of an energy scale ε) of the energy landscape from molecular dynamics simulations of a peptide substrate analogue of prolyl cis−trans isomerases. In order to do so, we develop and implement a model based on the position space analog of the Ornstein−Uhlenbeck process and Zwanzig’s theory of diffusion on a rough potential. This allows us to also probe an important property of the widely used atomistic simulation water models that directly affects the dynamics of biomolecular systems and highlights the importance of the choice of the water model in studying protein dynamics. We show that water contributes an additional roughness to the energy landscape. At lower temperatures this roughness, which becomes comparable to k B T, can considerably slow down protein dynamics. These results also have much broader implications for the function of some classes of enzymes, since the landscape topology of their substrates may change upon moving from an aqueous environment into the binding site.